PELATIHAN PENULISAN KARYA TULIS ILMIAH DALAM MENINGKATKAN KEMAMPUAN MENULIS PIMPINAN DAN KADER PK IMM FTIK UIAD SINJAI - Suriyati, Suriyati; Jamaluddin, Jamaluddin; Nur, Makmur Jaya; Zulfikar, Zulfikar (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
This research examines the effectiveness of scientific writing training in improving participants' writing skills. The training method is a direct practice approach with mentoring, intensive training, discussion, and reflection sessions. The instruments used to measure writing ability before and after training are scientific writing assessment rubrics and self-assessment questionnaires. The research results showed a significant increase in participants' writing abilities after attending the training. Before the training, most participants had limited writing skills, especially in writing structure, data presentation, and scientific argumentation. However, after the training, participants significantly improved written structure, argumentation clarity, and analysis depth. Apart from that, this training also helped participants to develop a critical attitude towards literature and hone their ability to integrate knowledge from various sources to support the argument. Participants also received positive responses regarding the interactive training methods and in-depth approach to scientific writing techniques. This research concludes that scientific writing training effectively improves participants' writing skills. Therefore, it is recommended that similar training focusing on various aspects of scientific writing be carried out to support the development of participants' academic and professional competencies.